2013
DOI: 10.1016/j.pain.2013.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Neural coding of nociceptive stimuli—from rat spinal neurones to human perception

Abstract: Translational studies are key to furthering our understanding of nociceptive signalling and bridging the gaps between molecules and pathways to the patients. This requires use of appropriate preclinical models that accurately depict outcome measures used in humans. Whereas behavioural animal studies classically involve reports related to nociceptive thresholds of, for example, withdrawal, electrophysiological recordings of spinal neurones that receive convergent input from primary afferents permits investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 46 publications
5
55
0
Order By: Relevance
“…36 The translation of DNIC acting on deep dorsal horn neurons to humans is supported by the fact that these spinal neurons code the intensity and spatial features of stimuli under the same anaesthetic conditions, in a manner remarkably parallel to human psychophysics. 28 Indeed, a recent study in patients with diabetic neuropathy showed that tapentadol restores CPM, exactly as we found here. 24 Descending controls appear to lack strict somatotopy.…”
Section: Discussionsupporting
confidence: 88%
“…36 The translation of DNIC acting on deep dorsal horn neurons to humans is supported by the fact that these spinal neurons code the intensity and spatial features of stimuli under the same anaesthetic conditions, in a manner remarkably parallel to human psychophysics. 28 Indeed, a recent study in patients with diabetic neuropathy showed that tapentadol restores CPM, exactly as we found here. 24 Descending controls appear to lack strict somatotopy.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, the recording of sensory spinal neurones under general anaesthesia allows suprathreshold stimuli, hence stimulation above the normal behavioural threshold, and so achieving levels of pain transmission that equate to the high pain scores that patients report. In fact, we have recently reported on the strong correlations between human pain ratings and the graded firing of these neurones under identical conditions (Sikandar et al, 2013). Very close parallels between both human pain perception and the human cortical response (electroencephalography measures) and spinal wide dynamic range (WDR) neuronal coding in rats were observed.…”
Section: Discussionmentioning
confidence: 69%
“…Although TRPM8-positive afferents terminate superficially in the dorsal horn (Takashima et al, 2007), deep dorsal horn WDR neurons receive these inputs from all fiber types either directly or indirectly through interneurons. We examined nociceptive processing in secondorder neurons in the deep dorsal horn, which respond to a wide range of stimuli in an intensity-dependent manner, a feature that correlates with nociceptive processing in humans (Sikandar et al, 2013). In naive rats, neither 30 nor 100 mg/kg M8-An significantly reduced lamina V/VI WDR neuronal responses to innocuous or noxious cold stimulation.…”
Section: Discussionmentioning
confidence: 99%